Harmonic Dark Pulse Emission in Erbium-Doped Fiber Laser - Tiu, Zian Cheak; Zarei, A.; Tan, S.J.; Ahmad, Harith; Harun, Sulaiman Wadi (Institute of Physics, 2015)
A harmonic dark pulse generation in an erbium-doped fiber laser is demonstrated based on a figure-of-eight configuration. It is found that the harmonic dark pulse can be shifted from the fundamental to the 5th order harmonic by increasing the pump power with an appropriate polarization controller orientation. The fundamental repetition rate of 20 kHz is obtained at the pump power of 29mW. The highest pulse energy of 42.6 nJ is obtained at the fundamental repetition rate. The operating frequency of the dark pulse trains shifts to 2nd, 3rd, 4th and 5th harmonic as the pump powers are increased to 34mW, 50mW, 59mW and 137mW, respectively.